Transporting Ability Calculation of the Rotor of Soil-Cultivating Loosening and Separating Vehicle - Syromyatnikov Yuriy; Kuts Aleksandr; Troyanovskaya Irina; Orekhovskaya Alexandra; Tikhonov Evgeny; Sokolova Viktoriia (Acta Technologica Agriculturae, 2022)
Currently, loosening and separating machines that combine the operations of crumbling and separating of soil according to the treated layer depth have come to the forefront. Interaction of the rotor blade of these machines with the soil comprises three stages: soil core formation; steady movement; and dumping of soil from the separating grid. The article determined the direction and magnitude of soil displacement, parameters and shape of the furrow formed after the ripper passage. Based on theoretical research, a mathematical model of the interaction of working bodies with the soil was developed. The initial data were obtained experimentally, and the model was justified. As a result, it was found that the supplied soil layer thickness and the fracture angle of ripper have the greatest influence on the transporting capacity of rotor ripper. Reducing the rotor blade entry angle into the soil from 45° to 30° made it possible to raise the second soil feed of the loosening and separating machine by more than 40 times. The width of rotor ripper practically does not affect the transporting capacity. Changing the angle of ripper entry into the soil allowed obtaining of the required transporting capacity of ripping and separating machine without changing the rotor design. Practical significance of the study lies in the possibility of increasing the work productivity without increasing its energy indicators.